Water Quality Profile of Yamuna River, India (Hydro Nepal: Journal of Water, Energy and Environment, 2009)
The water quality profile of a river represents the extent of its pollution in terms of health of a river with respect to its longitudinal direction. This paper deals with the water quality profile of north India’s Yamuna river using physico-chemical and bacteriological parameters that converge into a single value NSF WQI. The water quality map of the river has been prepared showing that the Delhi stretch is highly polluted due to dumping of waste and discharge of untreated sewage and industrial effluents. The water quality map is a useful tool for policy makers, decision makers and environmentalists to suggest and implement appropriate conservation measures to improve the health of the water body.Key words: Water quality; pollution; river profile; indices; mapping; Indiadoi: 10.3126/hn.v3i0.1914Hydro Nepal Journal of Water, Energy and Environment Issue No. 3, July 2008. Page: 19-24